A High-Throughput and Uniform Amplification Method for Cell Spheroids - Liu, Liyuan; Liu, Haixia; Huang, Xiaowen; Liu, Xiaoli; Zheng, Chengyun (Micromachines (Basel), 2022)
Cell culture is an important life science technology. Compared with the traditional two-dimensional cell culture, three-dimensional cell culture can simulate the natural environment and structure specificity of cell growth in vivo. As such, it has become a research hotspot. The existing three-dimensional cell culture techniques include the hanging drop method, spinner flask method, etc., making it difficult to ensure uniform morphology of the obtained cell spheroids while performing high-throughput. Here, we report a method for amplifying cell spheroids with the advantages of quickly enlarging the culture scale and obtaining cell spheroids with uniform morphology and a survival rate of over 95%. Technically, it is easy to operate and convenient to change substances. These results indicate that this method has the potential to become a promising approach for cell–cell, cell–stroma, cell–organ mutual interaction research, tissue engineering, and anti-cancer drug screening.